Strategi Kepala Sekolah Dalam Meningkatkan Kinerja Operator Terhadap Penggunaan DAPODIK di SMP Islam Al-Fatah Samarinda - muhamad abdulloh afandi; Dini Silmy Aulia; Sugiyono (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
This study aims to describe the strategies of the school principal in improving the performance of operators in managing the Data Pokok Pendidikan (DAPODIK) data. The results of this study are expected to provide valuable insights for school principals in formulating effective strategies to enhance operator performance in managing DAPODIK. This type of research is qualitative with a case study design. The subjects of the study are the school principal and the operators. Data collection techniques include observation, interviews, and literature review. Data analysis techniques involve data reduction, data display, drawing conclusions, and verification. The results of this study indicate that the strategies used by the school principal of SMP Islam Al Fatah Samarinda include (1) strategic planning; (2) training and competency development; (3) technical guidance implementation; (4) building communication and motivation; (5) providing adequate facility support; (6) monitoring; and (7) supervision and evaluation.